Evaluation of Selective Tibial Neurotomy for the Spastic Foot Treatment Using a Personal Goal-Centered Approach: A 1-Year Cohort Study. Issue 4 (23rd April 2023) - Dauleac, Corentin; Luaute, Jacques; Rode, Gilles; Afif, Afif; Sindou, Marc; Mertens, Patrick
Abstract : BACKGROUND: Selective tibial neurotomy (STN) has already demonstrated its effectiveness to reduce foot deformities and spasticity, but assessment according to a goal-centered approach is missing. OBJECTIVE: To evaluate the effectiveness of STN associated with a postoperative rehabilitation program for the treatment of the spastic foot, according to a goal-centered approach. METHODS: Interventional study (before-after STN and rehabilitation program) with observational design including consecutive adult patients with spastic foot, who received STN followed by a rehabilitation program, was performed. The primary outcome measure was the achievement of individual goals at the 1-year follow-up using the Goal Attainment Scaling methodology (with T-score). The secondary outcomes measures were the Modified Ashworth Scale and the modified Rankin Score. RESULTS: A total of 104 patients were included. At the 1-year follow-up, 228/252 (90.5%) goals were achieved: 62/252 (24.6%) were achieved as initially expected, 86/252 (34.1%) were achieved better than initially expected, and 80 (31.7%) were achieved much better than initially expected. The mean T-score was significantly increased at the 1-year follow-up (61.5 ± 10.5) compared with the preoperative period (38.1 ± 2.9, P < .00001), and 95/104 (91.3%) patients had a T-score ≥50, meaning that these patients have achieved their goals. At follow-up, spastic deformities were all significantly decreased ( P < .0001), the Modified Ashworth Scale was significantly lower for each muscle targeted ( P < .0001), and the modified Rankin Score was significantly decreased ( P < .0001) allowing the patient population to improve from a moderate to a slight disability status. CONCLUSION: This study showed that STN, associated with a postoperative rehabilitation program, successfully achieve personal goals in patients with spastic foot.